MAPPING THE EVOLUTION OF KNOWLEDGE ABOUT GENDER BIAS IN EDUCATIONAL ASSESSMENT: A BIBLIOMETRIC ANALYSIS - Mistiani, Wiwin (Musawa: Journal for Gender Studies, 2025)
This study aims to map the development of knowledge on gender bias in educational assessment through a bibliometric analysis based on Scopus data for the period 2000–2025. Based on the research problem, this study investigates temporal trends in publications, the most influential authors and journals, the geographic distribution of research, thematic structure based on keywords, and unfilled research gaps. Bibliometric methods were combined with a Systematic Literature Review (SLR) approach using PRISMA guidelines to ensure a comprehensive and structured analysis. A total of 109 selected articles were analyzed using VOSviewer 1.6.20 to map citation networks, author collaborations, and keyword clusters. The results show that publications on gender bias have increased significantly over the past two decades, with peak contributions coming from the United States, the United Kingdom, and European countries. Influential authors and journals are dominated by the medical and health education fields, shifting the research focus toward clinical assessment and competency-based measurement. Keyword analysis revealed five main thematic clusters: educational measurement, gender bias & psychological factors, inequality & equity, psychometric methodology, and simulation-based assessment. The findings also identify several research gaps, particularly the limited non-medical context, the scarcity of research from developing countries, the absence of local instruments, and the suboptimal study of intersectionality and education policy. This research contributes to a comprehensive map of the development of the global discourse on gender bias in assessment, while also offering new research directions relevant to the Indonesian context through strengthening local instruments, intersectionality studies, and pedagogical innovations to create a more equitable and gender-responsive evaluation system.